Dexmedetomidine Inhibits Voltage-Gated Sodium Channels via α2-Adrenoceptors in Trigeminal Ganglion Neurons - Im, Sang-Taek; Jo, Youn Yi; Han, Gayoung; Jo, Hyun Jung; Kim, Yong Ho; Park, Chul-Kyu (Mediators of Inflammation, 2018)
Dexmedetomidine, an α2-adrenoceptor agonist, is widely used as a sedative and analgesic agent in a number of clinical applications. However, little is known about the mechanism by which it exerts its analgesic effects on the trigeminal system. Two types of voltage-gated sodium channels, Nav1.7 and Nav1.8, as well as α2-adrenoceptors are expressed in primary sensory neurons of the trigeminal ganglion (TG). Using whole-cell patch-clamp recordings, we investigated the effects of dexmedetomidine on voltage-gated sodium channel currents (INa) via α2-adrenoceptors in dissociated, small-sized TG neurons. Dexmedetomidine caused a concentration-dependent inhibition of INa in small-sized TG neurons. INa inhibition by dexmedetomidine was blocked by yohimbine, a competitive α2-adrenoceptor antagonist. Dexmedetomidine-induced inhibition of INa was mediated by G protein-coupled receptors (GPCRs) as this effect was blocked by intracellular perfusion with the G protein inhibitor GDPβ-S. Our results suggest that the INa inhibition in small-sized TG neurons, mediated by the activation of Gi/o protein-coupled α2-adrenoceptors, might contribute to the analgesic effects of dexmedetomidine in the trigeminal system. Therefore, these new findings highlight a potential novel target for analgesic drugs in the orofacial region.